Padrões de variações espacial e temporal na estrutura funcional de assembleias de peixes em reservatórios Neotropicais. - Dias, Rosa Maria (2015)
The construction of hydroelectric and its associated reservoirs in large Brazilian rivers is the main source of disturbance to the ichthyofauna. Changes in the hydrological regime, food availability and habitats induce the reorganization of fish assemblages. Thus, it is expected that these changes will alter the trophic organization of the fish assemblages. Furthermore, the reservoir can act as an environmental filter and select certain functional traits after impoundment. Understanding how these processes occurs in Neotropical reservoirs provides a better understanding of how these impacts can act on the fish assemblage. This way, in the first approach, it was evaluated the trophic structure of fish assemblages in four Neotropical reservoirs, aiming to investigate its changes on the species richness, abundance and biomass in the different trophic guilds. The second approach considered the environmental conditions in the São Salvador reservoir - TO as an environmental filter for fish species from the impounded area, by selecting different functional traits among the zones of the reservoir and evaluating the functional diversity (RAO) in these areas. The main patterns found in the trophic guilds structure were an increase in the piscivorous richness in addition to decrease in herbivorous and insectivorous abundance and biomass, and increase of these attributes in the planktivorous guild. The other guilds showed distinct trends among the evaluated reservoirs. In regard to the functional traits, we found that the reservoir presented a longitudinal gradient of environmental conditions that were changed by damming the river. These different conditions among the zones indicated the selection of distinct functional characteristics of fish species. In the fluvial zone, the functional traits correlated with the most favored species were long distance migration behavior, piscivorous food habit and pelagic behavior. For the transition zone, the most affected species were those with functional traits related to pelagic and benthopelagic habitat, piscivorous and insectivorous guilds, and long distance migration behavior. In the lacustrine zone, the affected species were those with benthopelagic and long distance migratory behavior. The lacustrine zone presented the highest functional diversity, though that was the only zone were the functional diversity tended to decrease. Thus, it was found an increased functional diversity in the transition and fluvial zones after impoundment. This result was attributed to the displacement of species searching for environments with better survival conditions. The reservoir worked as an environmental filter selecting species with distinct functional traits among the considered zones.